Histomorphological features and prognosis of colitis-associated colorectal cancer in patients with primary sclerosing cholangitis. (November 2015) - Liu, Ganglei; Lin, Jingmei; Xie, Hao; Shen, Bo; Stocchi, Luca; Liu, Xiuli
Abstract Background. Histomorphology of colitis-associated colorectal cancer (CAC) in patients with primary sclerosing cholangitis (PSC) remains to be systemically characterized and prognosis in these patient needs to be further defined. Aim. To examine the impact of PSC on histomorphology and to assess prognosis of CAC-PSC patients. Methods. A cohort of CAC patients were identified from the Pathology Database (1994–2010) at Cleveland Clinic; histomorphological features and other relevant data were collected by retrospective review of pathology slides and medical records. Results. A total of 87 CAC patients were included, with 11 patients having PSC (the study group) and 76 patients without PSC (the control group). The overall median follow up was 6 (range: 0–20) years. The patients in the study group had a longer median duration of inflammatory bowel disease prior to CAC diagnosis (p = 0.046). In study group, seven (63.6%) patients had right-sided CAC (vs. 36.8% in the control group, p = 0.11). Background high-grade dysplasia was noted less (9.1% vs. 44.7%), while low-grade dysplasia was detected more in the study group (72.7% vs. 28.9%) (p = 0.02). All histomorphological features were comparable between groups. The overall survival (OS) and progression-free survival (PFS) showed no statistical difference between CAC patients with or without PSC. After excluding TNM stage IV patients, patients with PSC showed a trend toward shorter OS and PFS (p = 0.07 and p = 0.1). Conclusion. In CAC, histomorphology appeared to be independent of PSC. PSC is associated with a trend toward shorter OS and PFS in CAC patients with stage I–III diseases.